ANTIFUNGAL AND ANTIHEPATOTOXIC EFFECTS OF SEPIA INK EXTRACT AGAINST OXIDATIVE STRESS AS A RISK FACTOR OF INVASIVE PULMONARY ASPERGILLOSIS IN NEUTROPENIC MICE. - Fahmy, Sohair Ramadan; Soliman, Amel Mahmoud; Ali, Enas Mohamed (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: There is a great need for novel strategies to overcome the high mortality associated with invasive pulmonary aspergillosis (IPA) in immunocompromised patients. To evaluate the antifungal and antihepatotoxic potentials of Sepia ink extract, its effect on liver oxidative stress levels was analyzed against IPA in neutropenic mice using amphotercin B as a reference drug. Materials and Methods: Eighty neutropenic infected mice were randomly assigned into four main groups. The 1st group was treated with saline, neutropenic infected (NI), the 2nd group was treated with ink extract (200 mg/kg) (IE) and the 3rd group was treated with amphotericin B (150 mg/kg) (AMB) and 4th group was treated with IE plus AMB. Treatment was started at 24 h after fungal inoculation (1×109 conidia/ml). Results: The present study revealed good in vitro and in vivo antifungal activity of IE against A. fumigatus. IE significantly reduced hepatic fungal burden and returns liver function and histology to normal levels. Compared with the untreated infected group, mice in the IE, AMB, and IE+ AMB groups had increased glutathione reduced (GSH) and superoxide dismutase (SOD) and significantly reduced malondialdehyde (MDA) levels at 24 and 72 h after inoculation with A. fumigatus conidia. Conclusion: It is then concluded that in combination with antifungal therapy (AMB), IE treatment can reduce hepatic fungal burden, alleviate hepatic granulomatous lesions and oxidative stress associated with IPA in neutropenic mice .